Shedding Light at the Coalface: The Use of Socio-legal material in labour law teaching - Amanda Reilly (Legal Education Review)
[Extract] Student wellbeing is an extremely important issue in legal education today — there is little point in training law students if they become miserable in the process. The loss of a single law student or graduate through suicidal depression is one loss too many. The Tristan Jepson Memorial Foundation arose from one such occasion — a vibrant, promising young man and son, whose death triggered a realisation that friends and associates were having similar experiences. Being high achievers, depression and anxiety are viewed as weaknesses to be hidden. This in many ways only perpetuates the problem as it cuts off the sufferer from available medical assistance and willing support from friends and family.